FoodieCal: a convolutional neural network based food detection and calorie estimation system - Mashraf, Chowdhury Zerif; Ayon, Shahriar Ahmed; Yousuf, Abir Bin; Hossain, Fahad (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.